The Pauline writings a Sheffield reader - Evans, Craig A.; Porter, Stanley E. 1956- (Sheffield, UK Sheffield Academic, 1995)
Includes bibliographical references and indexes.
Articles originally published in Journal for the study of the New Testament
Keywords: Paul, the Apostle, Saint